Navigating Economic Shocks: The Role of Smoothing Behavior and Leverage in Manufacturing Profitability and Financial Risk - Martina, Mely; Wadi, Ikhwan (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to analyze the impact of income smoothing, consumption smoothing, and leverage on financial distress and profitability in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2023 period. The study employs a purposive sampling method to select samples based on specific criteria, resulting in 50 sample companies with a total of 200 observations. The research utilizes regression analysis with a mediation approach to identify both direct and indirect relationships among variables, using SmartPLS 4 software. The findings indicate that income smoothing has a negative but insignificant effect on financial distress and profitability. In contrast, consumption smoothing has a positive and significant impact on both variables. Meanwhile, leverage negatively affects financial distress but positively influences profitability. These findings highlight the importance of prudent financial management in ensuring stability and profitability in the manufacturing industry